ADJECTIVE WORD CLASS IN ENGLISH AND UZBEKISTAN - Rahimova Dilfuza Pulat kizi; Allayev Zafar Mingbo'ievich (International Journal of Literature and Language Studies, 2026)
Abstract : This in the article English The stylistic possibilities of lexical units belonging to the adjective word class in the Uzbek and Uzbek languages are studied in a comparative-typological manner. The expressive-emotional and stylistic functions of adjectives in artistic, journalistic and scientific styles are analyzed. As a result of the study, common and specific features of adjectives in the two languages are identified. stylistic features determined .